In-Vitro Evaluation of the Effect of MTA Setting on Apical Micro-leakage of Open Apex Canals with MTA Apical Plug - Samira Shahsiah; Mohammad Yazdizadeh; Sahar Jalali; Mansour Jafarzadeh; Pejman Pourakbar Jahandideh; Zeynab Buzarjomehri (Islamic Dental Association of Iran, 2013)
Background and Aim: Mineral Trioxide Aggregate (MTA) has a high clinical success rate when used as the apical plug. The conventional method of using MTA as an apical plug is doneduring two treatment sessions. This study aimed to evaluate the possibility of complete filling of root canal with gutta percha and AH26 sealer immediately after the placement of MTA plug .   Materials and Methods : A total of 88 single-rooted teeth were selected for this experimental study. The teeth were prepared and randomly divided into two groups of 40 each. Four teeth were considered as the positive control group and the remaining 4 as the negative controls. In group 1, MTA apical plug was placed, specimens were stored in saline solution for 24h and then filled with gutta percha and AH26 sealer. In the 2nd group, the roots were filled immediately after the placement of MTA. In the positive control group, the root canals were left unfilled and in the negative control group, root canals were filled with gutta percha and sealer. The specimens were then immersed in 1% methylene blue, demineralized in 5% nitric acid and cleared in methyl salicylate. Dye penetration was measured by a stereomicroscope in micrometer. T-test was used for statistical analysis .   Results: The mean dye penetration was 7813 μ m in the first and 9152 μ m in the second group. According to t-test, the 2nd group had significantly greater microleakage than the first group (P<0.05) .   Conclusion: MTA needs to be exposed to moisture for final setting and root canal obturation must be delayed until complete setting of MTA .